Men with disabilities – A cross sectional survey of health promotion, social inclusion and participation at community Men's Sheds - Wilson, N.; Cordier, R.; Parsons, R.; Vaz, S.; Buchanan, Angus (Elsevier, 2016)
Background: The intersections between chronicity, disability and social inequality are well understood. Novel ways to counter the social determinants of health and disability are needed. Men's Sheds are a community space where men can participate in a range of shared activities and potentially experience a health and social benefits. Objective This cross-sectional survey was conducted to inform future research by determining who attended Men's Sheds and the range of health, social, community, and educational activities undertaken there. This paper explores the membership of people with disabilities (PWD) at Men's Sheds and the factors that predict their membership. Methods: An online survey link was sent to all known Men's Sheds internationally in 2012. Data were analyzed using descriptive and inferential (univariate and multivariate) statistics. Results: 32.2% of international sheds and 29% of Australian sheds specifically targeted the inclusion of PWD. 80% of these sheds have significantly more members with disabilities than sheds who do no target PWD. Factors associated with greater membership of PWD included the provision of transport, social outings and promoting occupational skills. Conclusions: PWD are being encouraged to join and are joining Men's Sheds. This is significant as the value of participation and inclusion toward better health and wellbeing is well known. Men's Sheds offer a community space where the social determinants of chronicity and disability can potentially be countered.